PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA DI KELAS V MIN 2 KOTA MATARAM TAHUN PELAJARAN 2025/2026 - Yostisiah Maharani, Difla; Muammar; Silka Yuanti Draditaswari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low ability of students in writing poetry. The purpose of this study was to improve students’ poetry writing skills through the implementation of the inquiry learning model in Class V of MIN 2 Mataram City in the 2025/2026 Academic Year.nThis study employed Classroom Action Research (CAR). The research was conducted in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. Data collection techniques included interviews, observations, and oral tests. Quantitative data analysis was used to calculate the average score and classical completeness, while qualitative analysis was used to assess teacher and student activities. The indicators of research success included individual mastery, classical mastery, and the activities of teachers and students. The results showed that the implementation of the inquiry learning model was able to improve poetry writing skills in Class V of MIN 2 Mataram City in the 2025/2026 Academic Year. This was evidenced by the increase in the average class score from 67.40 with 36% classical completeness in Cycle I to 84.9 with 85% classical completeness in Cycle II. The improvement from Cycle I to Cycle II was 49%. Teacher activity also increased from 85.71% to 96.40%. This indicates that the research had achieved the predetermined indicators of success.